On a nonlocal boundary value problem of a coupled system of Volterra functional integro-dierential equations. - Noaman, Ysri; A.M.A, El-Sayed (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we study the existence of a unique solution for a nonlocal boundary- value problem of coupled system of Volterra functional integro-dierential equations.